Pengembangan Teknologi Pembelajaran PAI dalam Perspektif Al-Farabi: Metode Imitasi, Pembiasaan, dan Digitalisasi - Sriwiji Lestari; Saida Munawaroh; Rasti Astuti Laisaan; Sita Acetylena (Jurnal Wahana Literasi Pendidikan, 2026)
The rapid development of digital technology has brought significant transformation to Islamic Religious Education (PAI). However, digitalization risks obscuring the essence of value internalization and character building if it lacks a strong philosophical foundation. This study aims to conceptualize the development of PAI learning technology by integrating Al-Farabi’s philosophical thoughts, specifically through the methods of imitation (al-takhyil) and habituation (al-’adah) in the digital era. This study employed a qualitative method with a library research design. A content analysis approach was used to dissect Al-Farabi's texts, which were then synthesized with modern learning technology concepts. The findings indicate that Al-Farabi’s perspective is highly relevant to the digital architecture of PAI. First, the method of imitation is actualized through the utilization of multimedia technology, Virtual Reality (VR), and social media as interactive instruments for visualizing digital role models (uswah hasanah). Second, the method of habituation is integrated through gamification-based habit tracker applications and Artificial Intelligence (AI) to encourage the consistent repetition of commendable behaviors. This integration demonstrates that technology serves not merely as a tool for cognitive transfer, but as a dynamic platform for character building that adapts to contemporary times.